A study on the factors that influence students to plagiarize among undergraduate in higher learning institution: case study of UiTM Malacca City Campus / Siti Nurkhairina Kamarudin and Nur Shafika Liana Kamalia - Kamarudin, Siti Nurkhairina; Kamalia, Nur Shafika Liana (Faculty of Administrative Science and Policy Studies, 2013)
This study is aim to investigate the factors that influence students to plagiarize among undergraduate in UiTM Malacca City Campus. This study examines the relationship between four factors which are students’ attitude, Internet facilities, pressure and students’ awareness with the act of plagiarism. This study also tries to find out the most contributing factor that influence students to plagiarize in UiTM Malacca City Campus. Data collected are analyzed by using Statistical Package for the Social Science (SPSS) version 20.0. The techniques of data analysis used are descriptive statistics, reliability analysis, normality test, correlation statistics and regression analysis. The sample population is 357 respondents which involves UiTM Malacca City Campus students. All the respondents will answer the questionnaires which will provide the results of factors that influence students to plagiarize in UiTM Malacca City Campus. The result will be seen after using all the tests such as correlation analysis and regression analysis. Meanwhile, all the four factors of independent variables will be explained in the literature review and conceptual framework.